Hydrogenation of hydrogen peroxide over palladium/carbon in aqueous acidic medium containing different halide anions under static/flowing hydrogen - Choudhary, Vasant R.; Samanta, Chanchal; Jana, Prabhas (Industrial & Engineering Chemistry Research, 2007)
Kinetics of the hydrogenation of hydrogen peroxide (at 278 and/or 300 K) over Pd(5 wt%)/carbon in aqueous medium with or without containing acid or different halide anions (F-, Cl-, Br-, or I-) under static H-2 (i.e. batchwise) or flowing H-2 (i.e. semi-batchwise) at atmospheric pressure have been thoroughly studied. In the absence of protons or halide anions and also in the presence of F- anions, a very rapid decomposition of H2O2 (H2O2 -> H2O + 0.5O(2)) predominates over the H2O2 hydrogenation (H2O2 + H-2 -> 2H(2)O). However, in the presence of both the protons and Cl- or Br- anions, the H2O2 conversion occurs mainly by the hydrogenation reaction. The hydrogenation is found to be a zero-order reaction with respect to the H2O2 concentration, and its activation energy and frequency factor are strongly influenced by the halide anions. The hydrogenation is found to be more and more inhibited with increasing halide (Cl- or Br-) anion concentration. The cations associated with the halide anions have, however, only a very little influence on the hydrogenation. Iodide anions act as a very strong catalyst poison for the hydrogenation. In the presence of acid, the hydrogenation is very strongly influenced by the different halides, but, in the presence of halide anions (5.4 mmol/dm(3)), it is very mildly influenced by the different mineral acids (except HI). In the absence of protons, the Cl- and Br- anions are ineffective for inhibiting the rapid H2O2 decomposition. A role played by protons and halide anions for drastically inhibiting the rapid H2O2 decomposition is discussed.